Improving medication management for patients: the effect of a pharmacist on post-admission ward rounds. Issue 3 (2nd June 2005) - Fertleman, M; Barnett, N; Patel, T
Abstract : Problem: Medication management in the NHS has been highlighted by the UK Department of Health as an area for improvement. Pharmacist participation on post-take (post-admission) ward rounds was shown to reduce medication errors and reduced prescribing costs in the USA and in UK teaching hospitals, which can contribute to improved medication management. We sought to demonstrate the problem in our hospital by collecting data on prescribing practice from three consecutive general medical post-take ward rounds. Setting: Northwick Park Hospital, a district general hospital in north-west London, which provides acute medical services to a population of 300 000. Strategy for change: A pharmacist was invited to become a member of the post-take ward round team that reviewed medical patients admitted within the preceding 24 hours. Patients also continued to receive care from a ward based pharmacist. Patient notes were analysed for cost of drugs on admission and discharge, discrepancies between admission drug history and pharmacist history, number of admission drugs stopped before discharge, and pharmacist recommendations. Pharmacist recommendations and actions were classified using a National Patient Safety Agency risk matrix. Effects of change: Discrepancies between the admission and the pharmacist derived drug history were noted in 26 of 50 in the pre-intervention group and 52 of 53 in the intervention group. The annual drug cost per patient following discharge increased by £181 in the pre-intervention group and by £122 in the intervention group. Five pre-admission drugs were stopped in three pre-intervention patients saving £276 per annum, while the 42 drugs stopped in 19 intervention patients saved £4699 per annum. No ward based pharmacist recommendations were recorded in the pre-intervention group. Recommendations regarding drug choice, dose, and need for drug treatment were most common; 58 minor, 48 moderate and four major risks to patients were potentially avoided. Lessons learnt: The presence of a pharmacist on a post-take ward round improved the accuracy of drug history documentation, reduced prescribing costs, and decreased the potential risk to patients in our hospital. As a result of this work a full time pharmacist has now been funded to attend daily post-take ward rounds on a permanent basis.